Scalable Cell-Free Massive MIMO With Indoor/Outdoor Users - Felip Riera-Palou; Miquel Duran; Guillem Femenias (IEEE Open Journal of Vehicular Technology)
Cell-free networks are expected to be a forthcoming (r)evolutionary step in the coming generation of mobile networks, the so called 6 G. While mobile infrastructure is often assumed to be deployed outdoor by the operators, reality is that most of the traffic has at least one of the communication ends located indoors. This paper introduces the problem of providing wireless service to a heterogeneous population made of indoor and outdoor users using an outdoor cell-free massive MIMO (CF-mMIMO) infrastructure. It is shown how the pervasive max-min criterion (in cell-free setups) that results in near-uniform quality-of-service to all users may lead to catastrophic consequences when some of the users happen to be indoor. This problem is analyzed in both communication directions, uplink and downlink, exposing the similarities and differences of these two scenarios. Direction-specific solutions are then provided that involve improving the channel estimation and connectivity of indoor users and modifying the power allocation so as to somehow compensate for the wall propagation indoor users have to endure. All the techniques introduced satisfy the scalability requirements thus making our proposal realistically implementable.